Resilience and criminal justice: unsafe at low altitude - De Lint, Willem (Critical criminology, 2013)
Resilience is increasingly featuring in crime and justice policy discussions. It appears in the fusion of military, security and criminal justice. It offers an alignment by which individual actors are to be adaptive to the uncertain conditions of high risk societies. This article unpacks the application of resilience to criminal justice to reveal at least one negative implication: by placing the focus on self-directed change resilient subjects have limited transformative power. The concept of resilience involves discounting a longer view that challenges the dominant social institutions and orders of neoliberalism. In contrast, we propose the dignified subject and the re-assertion of the discounted institutional context at a level above the individual and community. This analysis supports renewing the transformative agenda of a critical criminology.